Correlation Analysis Between Watering Interval, Stem Height, Stem Diameter, And Number Of Leaves In Jackfruit Seedlings (Artocarpus Heterophyllus Lamk) - Umar Husein Abdullah; Nurfaizah Nurfaizah; Dewi Yana; Halim Akbar; Ruhalena Wilis; Elvrida Rosa (JERAMI : Indonesian Journal of Crop Science, 2024)
Meanwhile, the study entitled Correlation Analysis Between Watering Interval, Stem Height, Stem Diameter and Number of Leaves in Jackfruit Seedlings (Artocarpus Heterophyllus Lamk) is guided by the amount of watering of 100 ml which is based on the recommendation for the use of the best liquid fertilizer from the research of Mamik et al., (2020). The research will be carried out in the closed room experimental garden of the Plantation Management Study Program, Politeknik Indonesia Venezuela located in Cot Suruy Village, Ingin Jaya District, Aceh Besar Regency, from May 2024 to July 2024. The temperature in the experimental garden is set at 25oC – 28oC. To see the correlation analysis between the Watering Interval, Stem Height, Stem Diameter, and Number of Leaves in Jackfruit Seedlings (Artocarpus Heterophyllus Lamk) bivariate correlation analysis was used. There is a relationship between plant height, stem diameter, and number of leaves. There is no relationship between the length of the watering interval and the variables of plant height, stem diameter, and number of leaves. Table 6 shows that there are no variables that are strongly related and have a significant effect on the watering interval, plant height, stem diameter, and number of leaves. The decreasing amount of water causes plants to be unable to grow normally.